Rasionalitas Masyarakat Berbelanja Secara Konvensional di Era E-Commerce - Nurdin, Ibnu Phonna; Fajarni, Suci; Yulianda, Riki; Asri, Muh (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The existence of E-Commerce does not make people the main market for shopping. There are some major shopping problems with the E-Commerce system. This article aims to describe the rationality of people preferring conventional shopping over E-Commerce. This article is the result of field research carried out in Banda Aceh City. Research approach using qualitative methods. The research subjects are 10 informants, and data acquisition is produced through in-depth interviews and observations with conventional buyers selected through purposive techniques. Data analysis techniques in this study are: data reduction, data presentation, and conclusion drawing. The results of the study show that there are several forms of rationality why people do not shop in e-commerce, namely: products received do not match orders, high risk of buying electronic products in E-Commerce, delayed delivery of ordered goods, avoiding online fraud, and promotions that are bound to e-commerce. Therefore, the advantage that conventional markets have becomes the capital for their existence during the e-commerce market.